(untitled) (Fiep Bulletin - online, 2015)
Considering that the profissionalizing in Physical Education is recent, it started in 1998, is necessary identify and develop the abilities of professional insertion. This article intent to discuss the insertion of the Physical Education professional in the industry, especially working at the Ergonomic Area and intent to discuss if the general’s subjects of the graduation in this area permits that the graduated act in a satisfactory way at ergonomic which is a multidisciplinary area. We can observe that in the actuality companies are assuming a new thought related with the job market, looking for a great productivity in a low value, what makes the worker have an intense rhythm of work. We notice that the prevention is being adopted and in this view the ergonomic fits, that even the corrective character, presents as a prevention of the occupational diseases.